Octanol reductive amination catalyst with asymmetric coordination structure and preparation method of octanol reductive amination catalyst

By constructing a catalyst with a metal-oxygen asymmetric coordination structure on the LDHs support, the problem of difficulty in improving the activity and selectivity of the octanol reduction amination reaction under low hydrogen pressure conditions was solved, and the efficient progress of the octanol reduction amination reaction and the high selectivity of the octanol amine were achieved.

CN119746850APending Publication Date: 2025-04-04BEIJING UNIV OF CHEM TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411773314.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing catalytic technology for octanol reduction amination reaction is difficult to simultaneously improve the reaction activity and octanol selectivity under low hydrogen pressure conditions, mainly because the catalyst is difficult to balance the series process of alcohol dehydrogenation and imine hydrogenation.

Method used

Using layered composite metal hydroxides (LDHs) as support, by introducing reducing components and forming a metal-oxygen asymmetric coordination structure during the thermal topological transformation, it induces heterocratic activation of hydrogen, supports noble metal active components, and constructs asymmetric active sites to achieve efficient octanol reduction amination reaction.

Benefits of technology

The activity and selectivity of the octanol reduction amination reaction are significantly improved under low hydrogen pressure conditions. The active precious metals in the catalyst are highly dispersed, easy to recover and reuse, and have good reusability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005170775010000011
    Figure HDA0005170775010000011
  • Figure HDA0005170775010000012
    Figure HDA0005170775010000012
  • Figure HDA0005170775010000021
    Figure HDA0005170775010000021
Patent Text Reader

Abstract

The invention provides an octanol reductive amination catalyst with an asymmetric coordination structure and a preparation method of the octanol reductive amination catalyst. The octanol reductive amination catalyst is expressed as M1 (at) M2Ox / MgAlM2Ox or M1 / MgAlOx. M1 is a noble metal active component and is Ru or Pt; m2Ox is a component migrated from a laminate by a reducible component in the carrier through thermally induced topology, partially coats the active metal, and forms a metal-oxygen asymmetric coordination structure with the loaded M1 metal; mgAlM < 2 > O < x > and MgAlO < x > are used as carriers, and are composite metal oxides formed by thermally induced topology of MgAlM < 2 >-LDHs and MgAl-LDHs; the loading capacity of the M1 is 0.5 to 5 weight percent. The preparation method comprises the following steps: introducing metal ions containing reducible components and non-reducible metal ions into hydrotalcite, loading noble metal active components, and performing high-temperature reduction under the induction of a reducing atmosphere to obtain the catalyst. The catalyst shows high catalytic activity and high primary amine selectivity under low hydrogen pressure, and is good in stability and easy to recover.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of renewable resource biomass and fine chemical industry, and specifically relates to an octanol reductive amination catalyst with an asymmetric coordination structure and a preparation method thereof, and is mainly aimed at the reductive amination reaction of octanol. Background Art

[0002] For the reductive amination of octanol, the existing catalytic technology has the problems of low reaction activity and low selectivity of octylamine. The main reason is that the reductive amination reaction process of octanol is complicated and there is a scientific problem of difficult balance between dehydrogenation and hydrogenation. Specifically, octanol is first dehydrogenated to form aldehyde to start the reaction. The aldehyde is aminated to form C 8 Imine intermediate, this intermediate needs to be rapidly hydrogenated to prevent it from coexisting in large quantities in the reaction system, and then irreversibly dimerizes to secondary amine byproducts. To realize the rapid hydrogenation process of imines, increasing hydrogen pressure is the most common means. However, Le Chatelier's principle shows that excessive hydrogen pressure is not conducive to the dehydrogenation process of alcohol, which will have an adverse effect on the reaction activity. Therefore, the existing catalyst can only guarantee one of the high activity or high selectivity of the reaction because it is difficult to balance the series process of alcohol dehydrogenation and imine hydrogenation, so the overall yield is not high. To realize the dual improvement of the activity and selectivity of octanol reductive amination reaction, it is urgent to develop a new type of high-performance heterogeneous catalyst to realize the above-mentioned catalytic process under low hydrogen pressure conditions.

[0003] Analysis of the reaction process revealed that C 8 The rapid hydrogenation process of imine is mainly reflected in the hydrogenation of the C=N functional group in the imine molecule. C=N is a typical polar unsaturated functional group. Due to the difference in electronegativity between C and N elements (2.55 and 3.04), the electrons are unevenly distributed in the functional group. The N atom can attract electrons from the C atom and carry more negative charge, forming a C=N functional group. + =N - Electronic structure. For hydrogenation of polar unsaturated functional groups, H 2 Active H generated by heterolytic activation + and H - Compared with the homolytic activated H* radical, the heterolytic activated active hydrogen has a greater advantage because the charge distribution is also unequal, and it can attack the polar unsaturated functional groups through nucleophilic / electrophilic attacks, resulting in an increase in its hydrogenation efficiency. In the literature Organometallics 2010, 29, 1045-1048 and the literature Journal of American Chemical Society, 2005, 127, 7805-7814, researchers found that in the homogeneous catalytic system, the ionic form of heterolytic active hydrogen has a higher catalytic rate and selectivity in the hydrogenation process of C=N bonds. However, in the heterogeneous catalytic process, the catalyst has a higher affinity for H2 The activation of isolytic activity is more inclined to homolytic splitting into H*, because the electrons are evenly distributed in the hydrogen molecules, and the splitting process also follows the principle of equality. However, heterolytic activation requires a specific catalytic structure to induce uneven charge distribution, producing H + and H - The paper Zeolite-Encaged Isolated Platinum Ions Enable Heterolytic Dihydrogen Activation and Selective Hydrogenations, Journal of American Chemical Society, 2021, 143, 20898-20906 shows that researchers used Pt δ+ Species are encapsulated in Y-type molecular sieves to construct metal-base Pt δ+ -O 2- (MB, B=O,S,N,P) catalytic active center, which can adsorb single hydrogen atoms in hydrogen molecules respectively to achieve heterolytic activation of hydrogen molecules.

[0004] The above research foundation provides help for the rational design of high-performance alcohol reductive amination catalysts. In the catalyst design process, by structurally modifying and partially coating the metal active sites, the asymmetric coordination structure of the MB active sites can be controlled and the heterolytic activation of hydrogen can be induced, which is the key to achieving efficient hydrogenation of the C=N bond of imine under low hydrogen pressure conditions. This can not only ensure the smooth progress of the alcohol dehydrogenation process and guarantee the reaction activity, but also prevent the coexistence of a large number of imine intermediates in the reaction system, and quickly hydrogenate them to improve the reaction selectivity. Catalysts based on the above catalyst design strategy and with this structural characteristic have not yet been reported.

[0005] Layered double Hydroxides (LDHs) are a new type of inorganic functional material with the characteristics of adjustable layer cations and thermally induced topological transformation. At the same time, through the electrostatic adsorption of the layers, a high dispersion of the loaded active metals can be achieved. Therefore, LDHs is a multifunctional catalyst structural innovation platform and has attracted much attention in the field of heterogeneous catalysis. By utilizing the above structural characteristics, reducible components can be introduced into LDHs, and by utilizing the characteristics of thermally induced structural topological transformation, the reducible components can be partially migrated out of the layers and the loaded metal active centers can be modified and coated to a certain extent, thereby constructing a metal-oxygen, i.e., MO asymmetric coordination structure, inducing heterolytic activation of hydrogen.

[0006] The present invention intends to prepare a catalyst with a metal-oxygen asymmetric coordination structure based on the LDHs material platform and utilizing the material properties of LDHs. By inducing heterolytic activation of hydrogen, the efficient hydrogenation process of the imine C=N bond under low hydrogen pressure conditions is greatly enhanced, thereby improving the catalytic performance of the octanol reductive amination reaction under low hydrogen pressure reaction conditions. Summary of the invention

[0007] The purpose of the present invention is to provide a supported catalyst with an asymmetric coordination structure and a preparation method thereof. The catalyst is mainly used for the reduction amination reaction of octanol under low hydrogen pressure conditions.

[0008] The catalyst provided by the present invention is represented by M 1 @M 2 O x / MgAlM 2 O x or M 1 / MgAlO x Among them: "@" represents the coating, M 1 It is a precious metal active component, which is Ru or Pt, M 2 is a reducible metal ion, Ga 3+ or Ti 4+ ;M 2 O x It is a coating structure, which is a component that migrates from the layer plate through the thermal topology of the reducible component in the carrier, partially coating the active metal, and the range of x is 0.5-5; MgAlM 2 O x As the carrier, it is composed of MgAlM 2 -LDHs topologically formed composite metal oxides, x ranges from 0.5 to 5; M 1 The loading amount of M is 0.5-5wt%. 2 The amount of introduction is 0%-50%; when M 1 @M 2 O x / MgAlM 2 O x When the LDHs carrier is 2 Accounting for 0-50% of the mass fraction of the metal compound, when M 1 / MgAlO x In this case, the LDHs vector does not contain M 2 Component.

[0009] The specific preparation steps of the catalyst provided by the present invention are as follows:

[0010] A. Mg salt, Al salt and M 2 The salts were mixed and dissolved in deionized water, and ultrasonicated to fully dissolve them to obtain solution A, Mg salt, Al salt and M2 The amount of salt added depends on the MgAlM 2 -LDHs quantification, the anion in the solution is NO 3- , Cl - or SO 4 2 ;

[0011] Among them, M 2 The reducible metal ion Ga 3+ or Ti 4+ ; where M 2 0-50% by mass of the metal compound;

[0012] B. NaOH, NaNO 3 Dissolve in deionized water and mix thoroughly with ultrasonic to prepare a precipitant solution of equal volume to solution A, wherein NaOH and Na 2 CO 3 The concentrations of the precipitant solution and solution A are 0.05-0.5 mol / L and 0.01-0.1 mol / L respectively; the precipitant solution and solution A are added dropwise to a stirred reactor, and the molar number of the precipitant anion in the solution in the reactor is 1.2-1.5 times the molar number of the cation in solution A; the suspension is crystallized at a stirring rate of 60-120°C and 300-800rpm for 4-8 hours, and then separated by centrifugation. Wash with deionized water until the supernatant pH = 7, vacuum dry for 5-15 hours or dry at 60-80°C for 12 hours to obtain a series of MgAlM 2 -LDHs and MgAl-LDHs were ground into powder for later use; 2 It accounts for 0-50% of the mass fraction of the metal compound.

[0013] C. The precious metal M 1 The salt is dissolved in deionized water to prepare an immersion solution C with a concentration of 10-60 mmol / L; the M 1 The salt is RuCl 3 ·3H 2 O.Ru(NO)(NO 3 ) 3 , H 2 PtCl 6 One of them.

[0014] D. At 15-40°C and under magnetic stirring, the series of MgAlM prepared in step B was 2 -LDHs and MgAl-LDHs powders were dispersed in deionized water to form a suspension with a solid content of 0.05-0.1 g / ml; the suspension was then added to the impregnation solution C, and the impregnation solution C was 1The mass of the catalyst was 3.0% of the mass of the whole catalyst, and the mixture was stirred continuously and heated to 80-100°C until the deionized water was completely evaporated. The mixture was ground to obtain the catalyst loaded with M 1 The LDHs catalyst precursor powder is represented by M 1 / MgAlM 2 -LDHs or M 1 / MgAl-LDHs.

[0015] E. The M obtained in step D 1 / MgAlM 2 -LDHs or M 1 / MgAl-LDHs were heated to 300-600°C at a heating rate of 2-10°C / min in a reducing atmosphere and maintained for 3-6 hours, then cooled to room temperature and taken out to obtain M 1 @M 2 O x / MgAlM 2 O x or M 1 / MgAlO x Catalyst; the reducing gas is N 2 , Ar, He and hydrogen in a volume ratio of 1-10; the M 1 The load is M 1 The percentage of the sum of the mass fractions of metal and carrier.

[0016] The characteristics of the catalyst are: Catalyst M 1 @M 2 O x / MgAlM 2 O x or M 1 / MgAlO x In the process, the highly dispersed layer metal of the carrier has the function of anchoring the active components, which significantly improves the dispersion of the active components and makes them have a smaller particle size; at the same time, the reducible component M 2 After the introduction of LDHs, they will migrate out of the layer during the thermal topological transition and form a partial coating on the active metal. 1 The physical structure of the asymmetric active site is formed by coordination. According to the characteristics of the octanol reductive amination reaction, it is necessary to treat the C 8 Imine undergoes rapid hydrogenation, and H 2 The active metal required for activation. 2 After the introduction of LDHs, the asymmetric active site physical structure formed by the thermally induced topological transformation process can effectively promote the heterolytic activation of hydrogen to obtain H + and H -active species, thereby greatly improving the utilization rate of active hydrogen through nucleophilic / electrophilic attack and promoting the 8 The catalytic effect of the C=N functional group in the imine. Therefore, the catalyst M 1 @M 2 O x / MgAlM 2 O x It is possible to achieve a dual improvement in the activity and selectivity of octanol reductive amination reaction under low hydrogen pressure conditions.

[0017] Characterization of catalysts:

[0018] Figure 1 It can be seen that Ru is evenly dispersed on the surface of the carrier, with a particle size range of 2.0-7.0 nm and an average particle size of 5.07 nm. x The Ru nanoparticles were partially coated.

[0019] Depend on Figure 2 It can be seen that the Ru-O coordination ratio in this series of catalysts increases with the increase in the amount of Ti introduced, from 1.02 in Example 2 to 1.26 in Example 1.

[0020] Figure 3 It was shown that the octanol conversion rate reached 100% at 24 h, and the corresponding octylamine selectivity was 94% at 24 h.

[0021] Figure 4 It shows that the octanol conversion rate reaches 100% at 12 h, and the corresponding octylamine selectivity is 31% at 24 h.

[0022] Figure 5 It can be seen that Ru@TiO x / MgAlTiO x The catalyst has a strong ability to induce hydrogen heterolytic activation, and Ru / MgAlO x Catalyst no.

[0023] To ensure the accuracy of the reusability test, the reusability was tested within 6 h of the reaction. Figure 6 It shows that the catalyst was used continuously for 4 times, with octanol conversion rates of 34%, 35%, 35%, and 33%, and octylamine yields of 32%, 34%, 33%, and 32%, respectively, with no significant decrease in catalytic performance.

[0024] Beneficial effects of the present invention:

[0025] The present invention first prepares LDHs containing reducible metal components, uses the LDHs as a carrier, loads the noble metal active components, and then treats them at high temperature under the induction of a reducing atmosphere to make the active noble metal nanoparticles highly dispersed. 1The average particle size is 2.0-7.0nm and the dispersion is 20-50%. At the same time, the reducible components are induced to migrate out of the layer and partially cover the active metal particles to obtain Ru@TiO x / MgAlTiO x The catalyst can simultaneously realize the construction of Ru-O asymmetric coordination structure and the heterolytic activation of hydrogen.

[0026] The catalyst is used for the reductive amination reaction of octylamine under low hydrogen pressure feeding conditions. It has high activity and high selectivity for octylamine, outstanding catalytic performance, is easy to recover and reuse multiple times, and exhibits good reusability. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a spherical aberration corrected electron microscope (Ac-HAADF-STEM) photograph of the catalyst prepared in Example 1.

[0028] Figure 2 XAFS spectra of the R space of the catalysts prepared in Example 1, Example 2, Example 3, and Example 4.

[0029] Figure 3 These are the experimental results of the catalyst prepared in Example 1 in the reductive amination reaction of octanol, wherein a is the curve of octanol conversion versus time, and b is the curve of octylamine selectivity versus time.

[0030] Figure 4 These are the experimental results of the catalyst prepared in Example 2 in the reductive amination reaction of octanol, wherein a is a curve of octanol conversion versus time, and b is a curve of octylamine selectivity versus time.

[0031] Figure 5 HD exchange FT-IR spectra of the catalysts prepared in Example 1 and Example 2.

[0032] Figure 6 This is a bar graph showing the reusability of the catalyst prepared in Example 1 in the octanol reductive amination reaction. DETAILED DESCRIPTION

[0033] Example 1

[0034] A. 9 mmol Mg(NO 3 ) 2 6H 2 O,6mmol Al(NO 3 ) 3 9H 2 O,6mmol TiCl 4 and 80 mL of deionized water were fully dissolved under ultrasonic stirring until a stable and transparent mixed salt solution A was formed;

[0035] B. 0.064 mol NaOH and 0.028 mol NaNO 3 and 80 mL of deionized water were fully dissolved under ultrasonic stirring to form a stable and transparent alkaline solution B. The mixed alkaline solution B and the mixed salt solution A prepared in step A were added dropwise into a flask with a stirrer until a suspension was formed; the crystallization temperature of the suspension was controlled to be 80° C., the stirring rate was 400 rpm, and the crystallization time was 8 hours; the suspension was then centrifuged, the solid was washed with deionized water until the pH of the supernatant was 7, the solid was placed in an oven and dried at 80° C. for 12 hours, and ground to obtain MgAlTi-LDHs (Ti content was 24.93 wt%) powder;

[0036] C. RuCl 3 ·3H 2 O was dissolved in deionized water to prepare a concentration of 3 mg / ml RuCl 3 Impregnation liquid C (in Ru);

[0037] D. Under continuous stirring at 30°C, 0.97 g of MgAlTi-LDHs (Ti content of 24.93 wt%) powder in step B was added to 10 mL of deionized water to prepare a suspension; then 1000 μL of RuCl was added according to a noble metal loading of 3 wt%. 3 The impregnation solution C was stirred continuously and heated to 90 °C until the deionized water was completely evaporated to obtain LDHs powder loaded with noble metals, i.e., catalyst precursor, represented by RuCl 3 / MgAlTi-LDHs (Ti content is 24.93wt%);

[0038] E. The RuCl obtained in step D 3 / MgAlTi-LDHs (Ti content is 24.93wt%) in N with a volume fraction ratio of 10:1 2 / H 2 In the atmosphere at 5℃·min -1 The temperature was raised to 450°C at a rate of 1.5 °C, maintained for 3 h, then cooled to room temperature and taken out to obtain the catalyst. The catalyst was confirmed to be Ru@TiO x / MgAlTiO x (Ti content is 24.93wt%) catalyst, in which the actual loading amount of Ru is 2.56wt%, the average particle size of Ru is 5.07nm, and the dispersion degree is 10.85%.

[0039] The catalyst prepared above was used in the octanol reductive amination reaction experiment:

[0040] Weigh 250 mg of catalyst and put it into a high-pressure reactor with magnetic stirring, then add 15 mL of o-xylene and 2.0 mmol of octanol, fill with 0.55 MPa of ammonia at 25°C, then fill with hydrogen to 1 MPa, heat the reactor to 180°C, react for 36 hours, and take samples and analyze every 3 hours after reaching the temperature.

[0041] The reactant and product compositions of the samples were analyzed by gas chromatography using the internal standard method. Figure 3 .

[0042] The catalyst was then used 4 times to determine its reusability. Figure 6 .

[0043] Example 2

[0044] A. 9 mmol Mg(NO 3 ) 2 6H 2 O,6mmol Al(NO 3 ) 3 9H 2 O and 80 mL of deionized water were fully dissolved under ultrasonic stirring until a stable and transparent mixed salt solution A was formed;

[0045] B. 0.064 mol NaOH and 0.028 mol NaNO 3 and 80 mL of deionized water were fully dissolved under ultrasonic stirring to form a stable and transparent alkaline solution B. The mixed alkaline solution B and the mixed salt solution A prepared in step A were added dropwise into a flask with a stirrer until a suspension was formed; the crystallization temperature of the suspension was controlled to be 80°C, the stirring rate was 400 rpm, and the crystallization time was 8 hours; the suspension was then centrifuged, the solid was washed with deionized water until the pH of the supernatant was 7, the solid was placed in an oven and dried at 80°C for 12 hours, and ground to obtain MgAl-LDHs powder;

[0046] C. RuCl 3 ·3H 2 O was dissolved in deionized water to prepare a concentration of 3 mg / ml RuCl 3 Impregnation liquid C (in Ru);

[0047] D. Under continuous stirring at 30°C, 0.97 g of MgAl-LDHs powder in step B was added to 10 mL of deionized water to form a suspension; then 1000 μL of RuCl was added according to a 3 wt% noble metal loading. 3 The impregnation solution C was stirred continuously and heated to 90 °C until the deionized water was completely evaporated to obtain LDHs powder loaded with noble metals, i.e., catalyst precursor, represented by RuCl 3 / MgAl-LDHs;

[0048] E. The RuCl obtained in step D 3 / MgAl-LDHs in N with a volume fraction ratio of 10:1 2 / H 2 In the atmosphere at 5℃·min -1 The temperature was raised to 450°C at a rate of 1.5 °C, maintained for 3 h, then cooled to room temperature and taken out to obtain a catalyst. The catalyst was confirmed to be Ru / MgAlO by analysis. x The catalyst has an actual Ru loading of 2.55 wt%, an average Ru particle size of 5.21 nm, and a dispersion of 22.14%.

[0049] The catalyst prepared above was used in the octanol reductive amination reaction experiment:

[0050] Weigh 250 mg of catalyst and put it into a high-pressure reactor with magnetic stirring, then add 15 mL of o-xylene and 2.0 mmol of octanol, fill with 0.55 MPa of ammonia at 25°C, then fill with hydrogen to 1 MPa, heat the reactor to 180°C, react for 36 hours, and take samples and analyze every 3 hours after reaching the temperature.

[0051] The reactant and product compositions of the samples were analyzed by gas chromatography using the internal standard method. Figure 4 .

[0052] Example 3

[0053] A. 9 mmol Mg(NO 3 ) 2 6H 2 O,6mmol Al(NO 3 ) 3 9H 2 O,3mmol TiCl 4 and 80 mL of deionized water were fully dissolved under ultrasonic stirring until a stable and transparent mixed salt solution A was formed;

[0054] B. 0.064 mol NaOH and 0.028 mol NaNO 3 and 80 mL of deionized water were fully dissolved under ultrasonic stirring to form a stable and transparent alkaline solution B. The mixed alkaline solution B and the mixed salt solution A prepared in step A were added dropwise into a flask with a stirrer until a suspension was formed; the crystallization temperature of the suspension was controlled to be 80° C., the stirring rate was 400 rpm, and the crystallization time was 8 hours; the suspension was then centrifuged, the solid was washed with deionized water until the pH of the supernatant was 7, the solid was placed in an oven and dried at 80° C. for 12 hours, and ground to obtain MgAlTi-LDHs (Ti content was 12.44 wt%) powder;

[0055] C. RuCl 3 ·3H 2 O was dissolved in deionized water to prepare a concentration of 3 mg / ml RuCl 3 Impregnation liquid C (in Ru);

[0056] D. Under continuous stirring at 30°C, 0.97 g of MgAlTi-LDHs (Ti content of 12.44 wt%) powder in step B was added to 10 mL of deionized water to prepare a suspension; then 1000 μL of RuCl was added according to a noble metal loading of 3 wt%. 3 The impregnation solution C was stirred continuously and heated to 90 °C until the deionized water was completely evaporated to obtain LDHs powder loaded with noble metals, i.e., catalyst precursor, represented by RuCl 3 / MgAlTi-LDHs (Ti content is 12.44wt%);

[0057] E. The RuCl obtained in step D 3 / MgAlTi-LDHs (Ti content is 12.44wt%) in N with a volume fraction ratio of 10:1 2 / H 2 In the atmosphere at 5℃·min -1 The temperature was raised to 450°C at a rate of 1.5 °C, maintained for 3 h, then cooled to room temperature and taken out to obtain the catalyst. The catalyst was confirmed to be Ru@TiO x / MgAlTiO x (Ti content is 12.44wt%) catalyst, in which the actual loading amount of Ru is 2.60wt%, the average particle size of Ru is 4.77nm, and the dispersion is 16.22%.

[0058] The catalyst prepared above was used in the octanol reductive amination reaction experiment:

[0059] Weigh 250 mg of catalyst and put it into a high-pressure reactor with magnetic stirring, then add 15 mL of o-xylene and 2.0 mmol of octanol, fill with 0.55 MPa of ammonia at 25°C, then fill with hydrogen to 1 MPa, heat the reactor to 180°C, react for 36 hours, and take samples and analyze every 3 hours after reaching the temperature.

[0060] Example 4

[0061] A. 9 mmol Mg(NO 3 ) 2 6H 2 O,6mmol Al(NO 3 ) 3 9H 2 O,9mmol TiCl4 and 80 mL of deionized water were fully dissolved under ultrasonic stirring until a stable and transparent mixed salt solution A was formed;

[0062] B. 0.064 mol NaOH and 0.028 mol NaNO 3 and 80 mL of deionized water were fully dissolved under ultrasonic stirring to form a stable and transparent alkaline solution B. The mixed alkaline solution B and the mixed salt solution A prepared in step A were added dropwise into a flask with a stirrer until a suspension was formed; the crystallization temperature of the suspension was controlled to be 80°C, the stirring rate was 400 rpm, and the crystallization time was 8 hours; the suspension was then centrifuged, the solid was washed with deionized water until the pH of the supernatant was 7, the solid was placed in an oven and dried at 80°C for 12 hours, and ground to obtain MgAlTi-LDHs (Ti content was 30.34 wt%) powder;

[0063] C. RuCl 3 ·3H 2 O was dissolved in deionized water to prepare a concentration of 3 mg / ml RuCl 3 Impregnation liquid C (in Ru);

[0064] D. Under continuous stirring at 30°C, 0.97 g of MgAlTi-LDHs (Ti content of 30.34 wt%) powder in step B was added to 10 mL of deionized water to prepare a suspension; then 1000 μL of RuCl was added according to a noble metal loading of 3 wt%. 3 The impregnation solution C was stirred continuously and heated to 90 °C until the deionized water was completely evaporated to obtain LDHs powder loaded with noble metals, i.e., catalyst precursor, represented by RuCl 3 / MgAlTi-LDHs (Ti content is 30.34wt%);

[0065] E. The RuCl obtained in step D 3 / MgAlTi-LDHs (Ti content is 30.34wt%) in N with a volume fraction ratio of 10:1 2 / H 2 In the atmosphere at 5℃·min -1 The temperature was raised to 450°C at a rate of 1.5 °C, maintained for 3 h, then cooled to room temperature and taken out to obtain the catalyst. The catalyst was confirmed to be Ru@TiO x / MgAlTiO x The catalyst (Ti content is 30.34 wt%), wherein the actual loading amount of Ru is 2.65 wt%, the average particle size of Ru is 4.95 nm, and the dispersion degree is 6.91%.

[0066] The catalyst prepared above was used in the octanol reductive amination reaction experiment:

[0067] Weigh 250 mg of catalyst and put it into a high-pressure reactor with magnetic stirring, then add 15 mL of o-xylene and 2.0 mmol of octanol, fill with 0.55 MPa of ammonia at 25°C, then fill with hydrogen to 1 MPa, heat the reactor to 180°C, react for 36 hours, and take samples and analyze every 3 hours after reaching the temperature.

Claims

1. An octanol reductive amination catalyst having an asymmetric coordination structure, characterized in that: The catalyst is denoted as M1@M2O x / MgAlM2O x or M1 / MgAlO x ; Where: "@" represents coating, M1 is the active component of precious metal, which is Ru or Pt, M2 is the reducible metal ion, which is Ga 3+ or Ti 4+ ; M2O x It is a coated structure, partially coated with active metal, and the range of x is 0.5-5; MgAlM2O x The carrier is a composite metal oxide formed by MgAlM2-LDHs topology, the range of x is 0.5-5; the loading amount of M1 is 0.5-5wt%; and the introduction amount of M2 is 0%-50%.

2. A method for preparing a supported catalyst having an asymmetric coordination structure as claimed in claim 1, characterized in that The specific steps include: A. Mix and dissolve Mg salt, Al salt and M2 salt in deionized water, and dissolve them completely by ultrasound to obtain solution A. The amount of Mg salt, Al salt and M2 salt added is determined according to the MgAlM2-LDHs to be prepared. The anion in the solution is NO 3- , Cl - or SO4 2 ; Where M2 is a reducible metal ion Ga 3+ or Ti 4+ ; Wherein M2 accounts for 0-50% of the mass fraction of the metal compound; B. dissolving NaOH and NaNO3 in deionized water, and mixing them thoroughly by ultrasound to prepare a precipitant solution of equal volume with solution A, wherein the concentrations of NaOH and Na2CO3 are 0.05-0.5 mol / L and 0.01-0.1 mol / L, respectively; dropping the precipitant solution and solution A into a stirred reactor, and making the molar number of precipitant anions in the solution in the reactor 1.2-1.5 times the molar number of cations in solution A; crystallizing the suspension at a stirring rate of 60-120° C. and 300-800 rpm for 4-8 hours, and then separating it by centrifugation; washing with deionized water until the supernatant has a pH of 7, vacuum drying for 5-15 hours or drying at 60-80° C. for 12 hours, and obtaining a series of MgAlM2-LDHs and MgAl-LDHs, which are ground into powder for standby use; wherein M2 accounts for 0-50% of the mass fraction of the metal compound; C. dissolving a noble metal M1 salt in deionized water to prepare an impregnation solution C with a concentration of 10-60 mmol / L; the M1 salt is one of RuCl3·3H2O, Ru(NO)(NO3)3, and H2PtCl6; D. Dispersing the series of MgAlM2-LDHs and MgAl-LDHs powders prepared in step B into deionized water to form a suspension with a solid content of 0.05-0.1 g / ml at 15-40° C. and magnetic stirring; adding the suspension into the impregnation solution C, wherein the mass of M1 accounts for 0.5-5.0% of the mass of the whole catalyst, stirring continuously and heating to 80-100° C. until the deionized water is completely evaporated, grinding, and obtaining a LDHs catalyst precursor powder loaded with M1, expressed as M1 / MgAlM2-LDHs or M1 / MgAl-LDHs; E. The M1 / MgAlM2-LDHs or M1 / MgAl-LDHs obtained in step D was heated to 300-600°C at a heating rate of 2-10°C / min in a reducing atmosphere and maintained for 3-6 hours, then cooled to room temperature and taken out to obtain M1@M2O x / MgAlM2O x or M1 / MgAlO x Catalyst; the reducing gas is a mixture of one of N2, Ar, He and hydrogen in a volume ratio of 1-10.